Analysis and evaluation of efficiency indicators of operation of communication systems station equipment - Мачалин, Игорь Алексеевич (Ukrainian Information Security Research Journal, 2012)
The mathematical model of process of operation of telecommunication systems with using of the theory of recycling stochastic processes is offered. The indicator of average time of unscheduled removals of systems is defined. Estimates of influence of errors of checking on efficiency of operation of telecommunication systems are given.